A review on femoropopliteal arterial deformation during daily lives and nickel-titanium stent properties - K. Kareem, Ali; M. Gabir, Mustafa; R. Ali, Inas; E. Ismail, Al; Taib, Ishkrizat; Darlis, Nofrizalidris; M. Almoayed, Omar (Taylor & Francis, 2022)
The increasing number of studies on the behaviour of stent placement in recent decades provides a clear understanding of peripheral artery disease (PAD). The severe mechanical loads (axial tension and compression, bending, radial compression and torsion) deformation of the femoropopliteal artery (FPA) is responsible for the highest failure rate of permanent nickel-titanium (Nitinol) stents. Therefore, the purpose of this article is to review research papers that examined the deformation of the natural load environment of FPA, the properties of Nitinol and mechanical considerations. In conclusion, a better understanding of mechanical behaviour for FPA Nitinol stents contributes to increased mechanical performance and fatigue-life.